2007
DOI: 10.1071/rd07034
|View full text |Cite
|
Sign up to set email alerts
|

Cloning in companion animal, non-domestic and endangered species: can the technology become a practical reality?

Abstract: Somatic cell nuclear transfer (SCNT) can provide a unique alternative for the preservation of valuable individuals, breeds and species. However, with the exception of a handful of domestic animal species, successful production of healthy cloned offspring has been challenging. Progress in species that have little commercial or research interest, including many companion animal, non-domestic and endangered species (CANDES), has lagged behind. In this review, we discuss the current and future status of SCNT in CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 128 publications
0
18
1
Order By: Relevance
“…Dev. 58: [425][426][427][428][429][430][431] 2012) S ince the first cloned lamb was born, nuclear transfer (NT) has been challenging in several species and has produced many cloned offspring [1][2][3]. To produce cloned offspring, fetal fibroblasts have been chosen as a preferential donor cell line for NT so far because they have high proliferative potentials [4][5][6][7].…”
mentioning
confidence: 99%
“…Dev. 58: [425][426][427][428][429][430][431] 2012) S ince the first cloned lamb was born, nuclear transfer (NT) has been challenging in several species and has produced many cloned offspring [1][2][3]. To produce cloned offspring, fetal fibroblasts have been chosen as a preferential donor cell line for NT so far because they have high proliferative potentials [4][5][6][7].…”
mentioning
confidence: 99%
“…) and thus also necessary for embryo development. Previous studies on interspecies SCNT embryos have shown that poor developmental outcome may be attributed to disrupted communication between the nuclear and mitochondrial genomes of the different, albeit in most cases related, species (reviewed by Mastromonaco and King ). Establishment of xenomitochondrial homoplasmy, whereby an unrelated nucleus of one species interacts with the mitochondria of another, by Dey et al.…”
Section: Discussionmentioning
confidence: 99%
“…The species-specific nature of this organelle's biogenesis and utility makes it particularly relevant to functional iSCNT [30]. In concert with mitochondrial dysfunction, abnormal nuclear reprogramming is a major factor in failure of iSCNT to conserve endangered species [31].…”
Section: Discussionmentioning
confidence: 99%